1999
DOI: 10.1111/j.1945-5100.1999.tb01729.x
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy of the lunar crust: Results from Clementine

Abstract: Abstract-The central peaks of 109 impact craters across the Moon are examined with Clementine ultraviolet-visible (UVVIS) camera multispectral data. The craters range in diameter from 40 to 180 km and are believed to have exhumed material from 5-30 km beneath the surface to form the peaks, including both upper and lower crustal rocks depending on whether craters have impacted into highlands or basins. Representative five-color spectra from spectrally and spatially distinct areas within the peaks are classified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
313
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(341 citation statements)
references
References 42 publications
(53 reference statements)
24
313
2
Order By: Relevance
“…Plagioclase feldspar, the most abundant mineral in lunar highland rocks, is spectrally characterized by a continuous upward slope from the 415 to the 900 nm channel and then shows a decrease in reflectance between 900 and 1000 nm because of an absorption band at 1300 nm [Tompkins and Pieters, 1999]. Fresh highlands appear blue because they have a higher 415/750 value, which is the ratio displayed in the blue channel, compared to mature highlands soils.…”
Section: Clementine Calibration and Spectral Properties Of Lunar Marementioning
confidence: 99%
See 1 more Smart Citation
“…Plagioclase feldspar, the most abundant mineral in lunar highland rocks, is spectrally characterized by a continuous upward slope from the 415 to the 900 nm channel and then shows a decrease in reflectance between 900 and 1000 nm because of an absorption band at 1300 nm [Tompkins and Pieters, 1999]. Fresh highlands appear blue because they have a higher 415/750 value, which is the ratio displayed in the blue channel, compared to mature highlands soils.…”
Section: Clementine Calibration and Spectral Properties Of Lunar Marementioning
confidence: 99%
“…Fresh highlands appear blue because they have a higher 415/750 value, which is the ratio displayed in the blue channel, compared to mature highlands soils. Low-Ca pyroxene, which may be intermixed with the anorthosite in highlands rocks, should have an absorption at around 900 nm, slightly shorter than the highCa pyroxene absorption at 1000 nm [Tompkins and Pieters, 1999]. …”
Section: Clementine Calibration and Spectral Properties Of Lunar Marementioning
confidence: 99%
“…Despite heavy cratering, there are no broad areas within this region that have elevated FeO concentrations, with the main exception of Mare Moscoviense (Plate 1). Tompkins and Pieters [1999] showed that the central peaks of large craters within the FHT, which expose materials from as deep as 15 km, are dominantly anorthositic. Even some basins (e.g., Freundlich-Sharanov (18.5ĂžN, 175ĂžE), Hertzsprung (1.5ĂžN, 128.5ĂžW), and Korolev (4.5ĂžS, 157ĂžW)) in this region, which would have penetrated some 25-35 km, apparently did not excavate material that was substantially more mafic.…”
Section: Feldspathic Highlands Terranementioning
confidence: 99%
“…The original approach developed by Tompkins to distinguish between different mafic-bearing lithologies used two optical parameters to characterize the diagnostic shape of the ferrous band near 1000 nm: band strength (called "key ratio") and band curvature [Tompkins and Pieters, 1999]. In order to easily map the distribution of different lithologic units using the twodimensional data of Clementine color mosaics, we have expanded this scheme to include a third parameter, band tilt.…”
Section: Band Shapementioning
confidence: 99%